Validation of a short food frequency questionnaire specific for iodine in UK females of childbearing age. Issue 6 (13th March 2014) - Combet, E.; Lean, M. E. J.
Abstract Background Widespread subclinical iodine insufficiency has recently been reported in Europe, based on urinary iodine using World Health Organization/Food and Agriculture Organization criteria, in particular among young women. Although urinary iodine concentration (UIC) is a useful measurement of the iodine status in a population, it does not provide an insight into the habitual iodine intake of this population. This is compounded by the fact that very few iodine‐specific food frequency questionnaires (FFQ) have been validated so far. The present study aimed to develop and validate a new, simple, rapid survey tool to assess dietary iodine exposure in females of childbearing age. Methods Iodine was measured in a duplicate 24‐h urine collection. Iodine intake was measured with duplicate 4‐day semi‐quantitative food diaries and the FFQ. Correlation, cross‐classification and Bland–Altman analyses were used to estimate agreement, bias and the reliability of the method. The triangular (triad) method was used to calculate validity coefficients. Results Forty‐three women, aged 19–49 years, took part in the validation of the 17‐items FFQ. Median (interquartile range) UIC was 74 (47–92) μg L−1, which is indicative of mild iodine insufficiency. The FFQ showed good agreement with food diaries with respect to classifying iodine intake (82% of subjects were classified in the same or adjacent quartile). The FFQ was moderately correlated with the food diaries (rs = 0.45, P = 0.002) and urinary excretion in μg L−1 (rs = 0.34, P = 0.025) but not in μg day−1 (P = 0.316). The validity coefficients were 0.69, 0.66 and 0.52 for the food diaries, FFQ and urinary iodine excretion, respectively. Conclusions The FFQ provides a rapid and reliable estimate of dietary iodine exposure to identify those population subgroups at risk of iodine deficiency.